Comparative molecular signatures of human mesenchymal stromal cells during in vitro passaging / Aung Shuh Wen - Aung, Shuh Wen (2018)
Significant progress has been witnessed in the last decade documenting the use of human mesenchymal stem/stromal cells (hMSCs) as an alternative resource for cell replacement therapy owing to their intrinsic features of self-renewal and differentiation capacity into therapeutically valuable cell types. However, the yield of isolated hMSCs from donor tissues is usually inadequate, suggesting the need for the expansion of hMSCs in culture to meet the clinical need. However, hMSCs undergo cellular ageing, thus limiting their proliferation and differentiation potential in long term-culture. Cellular ageing is the manifestation of a complex interplay of molecular pathways between the gene expression and microniche which is govern by many processes including miRNA dysregulation. In this study, we aimed to determine molecular signatures of primary hMSCs isolated from deciduous pulp (SHED) and Wharton’s Jelly (WJSCs) associated with cellular ageing during in vitro passaging. We found phenotypic changes of primary hMSCs isolated from SHED and WJSCs by passaging in culture. Subsequently, molecular profiling showed a set of diverse miRNA and mRNAs that were deregulated in SHED and WJSCs. With this platform, an overlap of up-regulated and downregulated miRNAs between SHED and WJSCs was observed. Notably, the hsa-miR-22, hsamiR-485-5p and hsa-miR-let-7a have been identified as the cellular senescence inducers were show highly up-regulation. Whereas, hsa-miR-302a, hsa-miR-373 and hsa-miR-520e were found commonly down-regulation in both cell types. These miRNAs are known as signature miRNAs in stem cells involved in maintaining stemness biological process. Moreover, the predicted miRNA targets of both samples that captured in this study are show involved in modulate cellular activity by regulating many cellular processes including cell cycle, senescence, proliferative pathways, cell death and survival as well as metabolism related functions. Importantly, the integration analysis of miRNA/mRNA revealed that differentially expressed genes were associated with inflammatory signalling and cell cycle G2/M DNA damage regulation. The data presented here is in agreement with the basic characteristic studies iv which demonstrate the physiological changes of SHED and WJSCs during in vitro passaging. Taken together, it is intended that our study will contribute to the understanding of these miRNA/mRNA driving the biological process of cellular ageing in hMSCs. These will not only improve our fundamental knowledge of the ageing process but will also advance the development of a more effective and affordable targeted intervention approach for generating therapeutically valuable cell resources for treating many degenerative diseases.